EFFECTIVENESS OF DIFFERENT TYPES OF BONE GRAFTS AND PRF/CGF USED BY VARIOUS DEPARTMENTS IN A UNIVERSITY HOSPITAL SETTING - A RETROSPECTIVE STUDY - K, Monisha.; Murugan.P, Senthil; Kumar, Aravind (International Journal of Psychosocial Rehabilitation, 2020)
Bone grafts are used as a filler and scaffold to facilitate bone formation and promote wound heating. Grafts are usually bioresorbable and have no antigen-antibody reaction. Platelet Rich Fibrin(PRF) and Concentrated Growth Factor (CGF) are also used for surgical procedures to improve wound healing and promote tissue regeneration. At present the usage of these bone grafts and PRF/CGF has spread not only to oral and maxillofacial surgery and implantology but also in almost all the speciality dental departments like Periodontics, Prosthodontics and Endodontics. The aim of this study was to assess the type of bone grafts and PRF and CGF used in all departments of Saveetha Dental College and Hospital, Chennai.This Retrospective study was carried on one year period between June 2019 to April 2020 and on 66 patients (40 males and 26 Females) who reported to Saveetha Dental College and Hospital,Chennai.This final sample of 66 patients data were considered after analysing all the 86000 total patients records for the year 2019-2020 ,scrutinizing and fulfilling the inclusion and exclusion criteria. All available data was entered tabulated and entered in Excel sheets. The statistical analysis of Chi square test done through SPSS nd the significance level kept at p